Corruption distance and FDI in Africa - Tudane, Abiel (Research of GSB, 2018)
The majority of empirical studies that investigate the relationship of corruption and FDI tend to find that there is a strong relationship between corruption and FDI, although the findings are mixed in this regard; some have found the opposite while others have resulted in inconclusive results. This paper uses an institutional approach to corruption and seeks to advance the concept of "corruption distance" as it relates to FDI in context of Africa, it therefore investigated the manner in which the perceived level of corruption in the African continent affects the level of FDI counties in Africa are able to attract. The paper analyses corruption and FDI where the home countries are developing economies in Africa in order to obtain a greater insight regarding relationships in African investment using a panel data set of 45 African countries from 2003 to 2013. The research findings support the view that corruption distance has a negative effect on FDI in Africa. Given the levels of corruption in Africa, even expectations that more corrupt countries would be more likely to invest in less corrupt countries where confirmed. Our evidence confirms that the flow of FDI in Africa is mostly influenced by countries who on average are less corrupt that African countries. The paper finds that that there is a negative relationship between corruption and FDI where the home country is less corrupt than the host African country and concludes that the potential for FDI towards Africa to be great if the institutional quality underpinning the investment climate in African countries where to improve.